A Community-Based Research: Implementation Of Intensive Religious and Social Activities In Muallaf Village - Abdul Aziz Shidiq; Indra Indra; Ilham Tumanggor; Sopian Sinaga; Irham Dongoran; Dirja Hasugian (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
Sari Laba Jahe Village is a village of Biru-Biru sub-district, Deli Serdang district, North Sumatra province. This village is known as the village of Mualaf because the majority of Muslims in this village are converts. For the data on the religious community itself, Islam is actually a minority. The population in Sari Laba village reaches 1366 peoples. In Sari Laba village, the majority of them are Christians with a population of 759 Protestant Christians and 434 Catholic Christians while only 172 Muslims. When viewed from the Muslims themselves in this village, their number is only around 76 families and of these 76 families, 53 families consist of converts. Community service program student activities or KKL of Stai As-Sunnah began on 5-21 Ramadan 1442 H or 17 April - 3 May 2021. Many activities were carried out by students of Stai As-Sunnah during KKL activities. These activities are religious activities, related to social, related to education and management, as well as community empowerment. The KKL activities of the Stai-Assunnah students in Sari Laba village (mualaf village) are running smoothly and have a positive impact on the community.